2006
DOI: 10.1182/blood-2006-04-015743
|View full text |Cite
|
Sign up to set email alerts
|

Plasma inhibitory activity (PIA): a pharmacodynamic assay reveals insights into the basis for cytotoxic response to FLT3 inhibitors

Abstract: We have developed a useful surrogate assay for monitoring the efficacy of FLT3 inhibition in patients treated with oral FLT3 inhibitors. The plasma inhibitory activity (PIA) for FLT3 correlates with clinical activity in patients treated with CEP-701 and PKC412. Using the PIA assay, along with in vitro phosphorylation and cytotoxicity assays in leukemia cells, we compared PKC412 and its metabolite, CGP52421, with CEP-701. While both drugs could effectively inhibit FLT3 in vitro, CEP-701 was more cytotoxic to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
209
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(214 citation statements)
references
References 24 publications
3
209
0
2
Order By: Relevance
“…By contrast, the other metabolite, CGP62221, showed almost the same growth-inhibitory effects on neoplastic MC. Similar results have been described with AML cells (35). This is of particular interest as the percentage of MC in the primary samples varied among donors, and even if most non-MC lineage cells in advanced SM express KIT D816V, the response to TKI may be different in MC compared to other (clonal) cell types.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By contrast, the other metabolite, CGP62221, showed almost the same growth-inhibitory effects on neoplastic MC. Similar results have been described with AML cells (35). This is of particular interest as the percentage of MC in the primary samples varied among donors, and even if most non-MC lineage cells in advanced SM express KIT D816V, the response to TKI may be different in MC compared to other (clonal) cell types.…”
Section: Discussionsupporting
confidence: 75%
“…The non-linear pharmacokinetics of CGP62221 follows the same pattern as that of midostaurin, whereas the second metabolite, CGP52421, rises over time until reaching steady-state concentrations after one month of daily treatment (33)(34)(35)(36)(37). Our data show that CGP52421 is less effective in producing growth inhibition and apoptosis in neoplastic MC when compared to midostaurin.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, cardiac ventricular repolarization abnormalities have hampered the clinical development of quizartinib, but do not appear to be associated with crenolanib treatment (17). Previous work has suggested that binding of FLT3 TKIs by plasma proteins may negatively impact the their clinical efficacy (23). However, crenolanib potently inhibits FLT3-ITD and the common quizartinibresistant isoform FLT3-ITD/D835Y in the presence of human plasma at concentrations below those safely achieved in the firstin-human trial.…”
Section: Discussionmentioning
confidence: 95%
“…Other in vitro studies have confirmed the association between the nonselectivity of the FLT3 inhibitors midostaurin and lestaurtinib and increased leukemic cell death. 81 Resistance to FLT3 inhibitors can occur, primarily through upregulation of the FLT3 receptor, 82 point mutations 83 or increased FLT3 ligand levels. 60,61 In vitro screens have identified four mutations in the ATP-binding pocket of FLT3 that confer varying degrees of resistance to FLT3 inhibitors.…”
Section: Quizartinib (Ac220)mentioning
confidence: 99%